BLOOD DRAWING PRACTICES AND BLOOD LOSS FROM LABORATORY TESTS Y TESTS - SHANKAR MANOHAR PAWAR; E. PRABHAKAR REDDY; A. VAITHILINGAM; G. R. CHAUDHARI; G. SURYA PRAKASH (The Bioscan, 2010)
In the Intensive care unit (ICU), arterial access lines can make phlebotomy easier and less painful for patients. With this ease of phlebotomy has come a perceived tendency toward ordering frequent blood tests by physicians, sending frequent blood specimens by nurses, and asking for resubmitted samples by the laboratory. This might lead to significant increases in the cost of a stay in the ICU. Laboratory tests can be an important source of blood loss in hospitals, especially for new borns and patients in intensive care. Anemia caused by repeated blood withdrawals is a common problem in hospitalized patients particularly those who are critically ill or rare receiving various medications. Laboratory persons also should look at the volumes and to make sure only the amounts that are necessary for the tests. Actual laboratory instruments use small amounts of sample, often in the range of 3 to 100 ì L, but it is common practice to draw full large-volume tubes, regardless of tests requested and amount of sample required. To conclude, blood loss from diagnostic tests could be reduced by newly developed selective analyzers, smaller sample volumes, blood saving collection techniques and to collect only the necessary amount of blood needed for tests.